Optimization of Energy Consumption in Acetic Acid and N-Butanol Esterification Reaction with Simultaneous Water Removal Using Novel Microcontroller Based Automated Reactor (Chemical Engineering Research Bulletin, 2020)
This paper focuses on the optimization of energy consumption in esterification of acetic acid wherein the water removal is achieved by using silica gel desiccant in a microcontroller based automated reactor. Esterification reactions are endothermic hence, one can get more product, by increasing the temperature, thus disturbing the equilibrium. Heat of reaction (Hr) was estimated by using the heat capacity data and constants (C). Energy analysis and modelling was developed for the enhancement of process which is the key component of the systems. The mathematical model is validated by experimental results. In this paper, effect of parameters like desiccant weight, regeneration temperature and molar ratio on energy consumption are studied. Trends of energy effectiveness of several parameters are presented in the various regeneration temperatures and molar ratio and desiccant weight which confirmed the linear relationship with hot air flowrate. Decrease of 33% in power consumption was observed by decreasing the hot air flowrate by 10%.This is the conformity of validation of affinity law. The newly invented model was optimized for variables, hot air temperature, molar ratio and silica gel weight. The minimum energy consumption at 1 desirability was reported by software in the given range of parameters. When the hot air temperature, molar ratio and silica gel weight were 67.670C, 3 and 34.32 gm, then the minimum value of energy consumption was 29.59 Watt.Chemical Engineering Research Bulletin 21(2019) 46-57